Fate of respiratory droplets in tropical vs temperate environments and implications for SARS-CoV-2 transmission (2020)
The new pandemic of SARS-CoV-2 has shown stark differences in number of affected patients between countries in the tropics and those with temperate environments. Though there have been many theories on reasons for these differences, we hypothesise that this could be due to differences in the fate of respiratory droplets in the two environments. A simple understanding of the mechanics of droplet size, dispersion and displacement could help infection control and public health measures to minimize spread and mitigate the risk of people getting infected especially in hotspots like hospital environments or other closed spaces. This paper discusses the possibility of differences in number of infections and spread between different countries based on the spread of droplets.